Between Coercion and Representation: Exploring Variation in Support Relations between Tamil Civilians and the Liberation Tigers of Tamil Eelam (LTTE) - Meier, Larissa Daria (PARTECIPAZIONE E CONFLITTO, 2022)
This article explores the multi-faceted, contextual, and ambivalent character of support relations between the LTTE and Tamil civilians. It demonstrates how distinct support patterns emerge from particular power constellations and manifestations of violence in the localities where respondents lived and interacted with the LTTE. The social ties between respondents whose political socialization was shaped by the escalation of the conflict and who, later, lived in government controlled areas were predominately based on a sense of political representation and characterized by subtle notions of socio-spatial distance; by contrast, for interviewees living in militarily contested zones, fear and coercion but also affective connections to LTTE members played a crucial role in their interactions with and orientations towards the LTTE. Lastly, in LTTE controlled areas, notions of support oscillated between perceptions of effective service provision and fear of recruitment.